Wetting of the microporous layer at the cathode of an anion exchange membrane water electrolyzer - Raziyeh Akbari; Marta Mastrosimone; Mohsin Muhyuddin; Tommaso Caielli; Piercarlo Mustarelli; Carlo Santoro; Carlo Antonini (Materials for Renewable and Sustainable Energy)
Abstract Water management is crucial for the performance of anion exchange membrane water electrolyzers (AEM-WEs), to maintain membrane hydration and enable phase separation between hydrogen gas and liquid water. Therefore, careful material selection for the anode and cathode is essential to enhance reactant/product transport and optimize water management under ‘dry cathode’ conditions. This study investigates the wetting characteristics of two commercially available porous transport layers (PTLs) used in AEM-WE: carbon paper and carbon paper with a microporous layer (MPL). Wettability was measured under static, quasi-static, and dynamic conditions to assess the effect of water and electrolytes (NaOH, KOH, K2CO3) across concentrations (up to 1 M) and operational temperatures (20 °C to 92 °C). Carbon paper exhibits mild hydrophobicity (advancing contact angles of $$\:\sim$$ 120°, however with receding contact angle $$\:\sim$$ 0°), whereas carbon paper with MPL demonstrates superhydrophobicity (advancing and receding contact angles >145° and low contact angle hysteresis), maintaining a stable Cassie-Baxter wetting state. Dynamic wetting experiments confirmed the robustness of the superhydrophobicity in carbon paper with MPL, facilitating phase separation between hydrogen gas and liquid water. The presence of supporting electrolytes did not significantly affect wettability, and the materials retained hydrophobic properties across different temperatures. These findings highlight the importance of MPLs in optimizing water transport and gas rejection within AEM-WEs, ensuring efficient and stable operation under “dry cathode” conditions. These PTLs (with and without the addition of the MPL) were integrated into AEM-WE and polarization curves were run. Preliminary data, in a specific condition, suggested the presence of the MPL within the PTL enhance AEM-WE performance.